Offering Dimensions in Service Business with Analytic Hierarchy Process - Väisänen, Mikko (My University, 2010)
In this thesis the total offering package of the case company was surveyed with Analytic Hierarchy Process method. The objective was to define the essential criteria of the offering package, evaluate their weights compared to each other and formulate the understanding of the offering package the case company is providing but also what offering criteria the customers are appreciating. In addition the goal was to study and define the competitors of the case company in the market area, to compare their offering package and to find areas of development in the offering package of the case company. Analytic Hierarchy Process model was constructed based on defined criteria on December 2009 and the enquiry process within case company and its customers was executed on January 2010. The enquiry was done globally by the preselected people, in whose area of business the products and services offered by the case company are included. The enquiry results were analyzed by using the academic licence of the commercial software Expert Choice. The software was selected for suitability reasons. The results can be sorted on three main categories; first on congruent study of the total offering package criteria weighting, secondly on competitors analysis with aforementioned criteria and thirdly on further additional analysis with information gathered from the open questions. In the thesis the importance of the service dimension was discovered since both parties judged it as the most important criteria of the offering package. On sub-criteria however, distinct differences were discovered between the weighting of the case company and customer criteria. Also in comparison between competitors differences were detected and new information about how the customer is experiencing the added value on each criterion was found. The open questions added dept to the formulated insight on the offering package and brought out some specific matters the customers have perceived or would value to experience on interaction with the providers. As a result some action and further development proposal were sponsored.
Keywords: Analytic Hierarchy Process; Service business; Offering package; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|